Management of Regional Government Information Systems (SIPD) at the Regional Secretariat of District Minahasa - Goni, James Andrew Adrian; Sendouw, Recky HE; Mandagi, Marthinus (International Journal of Information Technology and Education, 2022)
The study seeks to learn more about the SIPD administration at the Planning and Finance Section of the Regional Secretariat of Minahasa Regency. In this study, a qualitative methodology is combined with a descriptive technique. Techniques for collecting data include observation, interviewing, and documentation. strategies for data processing that include steps for data presentation, data reduction, and data verification. In the planning, budgeting, and reporting or evaluation of procedures, the Regional Secretariat's management of the Regional Government Information System (SIPD) is highlighted in this study. SIPD encountered challenges, including issues with human resources, supporting infrastructure, such as the internet network, and flawed SIPD apps, which hindered its implementation. The Secretariat of Minahasa District's SIPD management has been successful, according to the findings of the research, it can be said. Additionally, it is advised that the Regional Government expand human resource capacity and enhance infrastructure and supporting facilities, while also urging the Central Government to perfect the SIPD application.